Case report: A rollercoaster journey of pemphigus vegetans - Hou, Xiaoyuan; Chen, Jia (Frontiers in Immunology, 2025)
Pemphigus vegetans (P Veg), the rarest subtype of pemphigus, is characterized by vegetative plaques, primarily affecting intertriginous areas. The most common autoantibodies target desmoglein 3 (Dsg3). A 60-year-old female patient presented with well-demarcated red vegetative plaques on her feet, vulva, and thigh, accompanied by surrounding pustules. Histopathological examination revealed epidermal hyperplasia with significant infiltration of neutrophils and eosinophils in the dermis. Enzyme-linked immunosorbent assay showed elevated anti-Dsg3 antibodies (203.2 U/ml), and immunohistochemical staining confirmed positive expression of anti-Dsg3 IgG antibodies in keratinocytes. The patient was diagnosed with P Veg and achieved remission after treatment with either 900 mg of intravenous spesolimab or oral methylprednisolone.